2021
DOI: 10.1007/s40843-021-1713-x
|View full text |Cite
|
Sign up to set email alerts
|

Polarized upconversion luminescence from a single LiLuF4:Yb3+/Er3+ microcrystal for orientation tracking

Abstract: Polarized upconversion luminescence (UCL) of lanthanide-doped micro/nano-crystals has shown great promise in single-particle tracking and super-resolution bioimaging. However, because of the spectral line broadening and multiple sites of lanthanide in upconversion particles (UCPs), the crystal-field (CF) polarization components of UCL are usually undistinguishable. Herein, we report the linearly polarized UCL in LiLuF 4 :Yb 3+ /Er 3+ single microcrystals with resolvable CF transition lines and a polarization d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [107][108][109][110][111] To make use of polarized UCL, Paloma et al reported using microsized upconverting particles (UCP) to monitor the suspending medium in real-time via singleparticle spectroscopy. [112] Single UCP was optically trapped and maintained at a certain position, followed by the excitation of linearly polarized 980 nm laser (Figure 10b).…”
Section: Regulating Upconversion By Different Polarization Anglementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [107][108][109][110][111] To make use of polarized UCL, Paloma et al reported using microsized upconverting particles (UCP) to monitor the suspending medium in real-time via singleparticle spectroscopy. [112] Single UCP was optically trapped and maintained at a certain position, followed by the excitation of linearly polarized 980 nm laser (Figure 10b).…”
Section: Regulating Upconversion By Different Polarization Anglementioning
confidence: 99%
“…In this context, some other groups also reported the polarized UCL from NaYF 4 , LiYF 4 , and LiLuF 4 UCNPs. [ 107–111 ] To make use of polarized UCL, Paloma et al. reported using microsized upconverting particles (UCP) to monitor the suspending medium in real‐time via single‐particle spectroscopy.…”
Section: Remote Regulation Of Upconversionmentioning
confidence: 99%
“…Using an optical beam, one can further trap single LiYF 4 :Yb 3+ /Er 3+ microparticles in three different spatial orientations, which allowed for its polarized emission to be probed at two different angles, θ = 56° and 90°. Recently, the crystal-field (CF) polarization components of a class of bipyramidal LiLuF 4 :Yb 3+ /Er 3+ microcrystals with a mean size of ∼20 μm × 12 μm has been determined by SPPS . The resolved CF components include transitions from the 2 H 11/2 (515–530 nm), 4 S 3/2 (538–554 nm), and 4 F 9/2 (645–675 nm) multiplets to the 4 I 15/2 ground state of Er 3+ , corresponding to emission peaks with full-width at half-maximum less than 0.70 nm.…”
Section: Current Implementation Of Upconverting Nanoparticles In Stim...mentioning
confidence: 99%
“…Recently, the crystal-field (CF) polarization components of a class of bipyramidal LiLuF 4 :Yb 3+ /Er 3+ microcrystals with a mean size of ∼20 μm × 12 μm has been determined by SPPS. 34 The resolved CF components include transitions from the Here I 1 and I 2 are the luminescence intensity from two thermally coupled energy levels, E 1 and E 2 , respectively. I 2 /I 1 follows Boltzmann distribution, C is a constant, ΔE is the energy gap between the two excited states, k B is the Boltzmann constant, and T is the absolute temperature.…”
Section: Nanoparticles In Stimuli Sensingmentioning
confidence: 99%
“…Detection of the 3D orientation is critically important for applications, and the orientation tracing would be attractive for interaction and structural dynamics studies . There are now optical technologies for obtaining the 3D orientation, such as defocusing imaging , and fluorescence polarization microscopy. , Although polarized UC emission was observed, , the exact correlation between the polarization and the orientation of crystal has not been established. From the discussions presented above, the in-plane orientation of crystals can be obtained from θ p (Figure ).…”
mentioning
confidence: 99%